HATRA: THREE NOTES, HISTORICAL, ICONOGRAPHICAL, AND RELIGIOUS. (December 2021) - al-Salihi, Wathiq
Abstract : Historical Note: The chronological table of rulers of Hatra includes an ambiguous person named Wrwd mrya, who supposedly succeeded Nshryhb mrya . Is he the latter's younger brother or older son? The epigraphical and sculptural evidence suggest that Nşru mrya, who followed Wrwd, is the son of Nshryhb mrya and was in fact Wrwd himself, who acquired the epithet or appellative Nşru, meaning the winner, protector, and defender. This epithet reflects that he led the Hatrenes and Arab tribes in their defence against the Roman army of Trajan in 116/117 A.D. Wrwd/Nsru commemorated his victory in a relief lintel in Shrine V at Hatra. Iconographical Note: The excavators of Shrine I discovered the famous sculptured slab known as the Cerberus relief, depicting a god of the underworld with snakes and scorpions, thought to be an image of Nergal. However, the excavation of Shrine II revealed an altar, one side of which is carved in relief with a similar underworld deity with snakes. The other side of the altar is incised with an inscription mentioning a god Zqyqa . Thus, Zqyqa at Hatra is the god of the underworld, rather than Nergal. Religious Note: An enigmatic statue was discovered in Shrine I, depicting a standing horned male. On the base is an Aramaic inscription mentioning the name Kenzw ; he was identified as an 'unknown god'. The excavation of Building A by an Italian team discovered a horned male statue with an inscription that referred to him as Hpyzw . It was originally placed on a podium set against the façade of the house courtyard. In front of the podium was an altar and evidence of ashes and burnt offerings. This context indicates that the horned statue of Hpyzw was worshipped and offerings were presented to him as a founder of the household. The similarity of the two statues suggests that a type of ancestor worship was practised at Hatra.